Is multi-party coalition government better for the protection of socially backward classes in India? - Kaushik Basu; Sattwick Dey Biswas; Pratik Harish; Sasi Dhar; Mounik Lahiri (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
The paper investigates whether multi-party coalition government is better for the protection of socially backward classes, i.e. Scheduled Castes, in India. We have looked at the impact of types of government on the reduction of the gap between Scheduled Castes and Upper Castes in terms of various socio-economic indicators. Our analysis suggests that single-party majoritarian government is better at reducing the gap in terms of poverty and school drop-out rates, improves the employment scenario, and reduces the distressed migration. Nevertheless, neither single-party majoritarian government nor coalition government is able to reduce the gap in relation to institutional delivery, inequality, and land holding.
Keywords: C01; C23; 330; single-party majoritarian government; multi-party coalition government; inequality; Scheduled Castes; social protection; panel data; India